2020
DOI: 10.1080/0886022x.2020.1792315
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of primary membranous nephropathy based on serum anti-phospholipase A2 receptor antibodies and glomerular phospholipase A2 receptor antigen status: a retrospective cohort study

Abstract: Huang (2020) Outcomes of primary membranous nephropathy based on serum anti-phospholipase A2 receptor antibodies and glomerular phospholipase A2 receptor antigen status: a retrospective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…In line with other reports, we were unable to find significant differences in baseline clinical phenotype or outcome between anti-PLA2R antibody positive and negative patients in the original cohort [ 14 , 15 ]. In contrast, other studies reported that patients with anti-PLA2R antibodies negative MN had a better prognosis, with higher chances of achieving a clinical remission and a faster decline of proteinuria compared to patients with positive anti-PLA2R antibody [ 16 , 17 ]. However, these studies are limited by the relatively small number of patients with negative anti-PLA2R antibody included (10 and 13, respectively) [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In line with other reports, we were unable to find significant differences in baseline clinical phenotype or outcome between anti-PLA2R antibody positive and negative patients in the original cohort [ 14 , 15 ]. In contrast, other studies reported that patients with anti-PLA2R antibodies negative MN had a better prognosis, with higher chances of achieving a clinical remission and a faster decline of proteinuria compared to patients with positive anti-PLA2R antibody [ 16 , 17 ]. However, these studies are limited by the relatively small number of patients with negative anti-PLA2R antibody included (10 and 13, respectively) [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, other studies reported that patients with anti-PLA2R antibodies negative MN had a better prognosis, with higher chances of achieving a clinical remission and a faster decline of proteinuria compared to patients with positive anti-PLA2R antibody [ 16 , 17 ]. However, these studies are limited by the relatively small number of patients with negative anti-PLA2R antibody included (10 and 13, respectively) [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 94%
“…As an alternative to diseasespecific chronicity scores [5][6][7], the MCCS was proposed as a standardized pathology scoring system to address chronic changes in native kidney biopsies in a more uniform way, regard- less of the underlying diagnosis. The prognostic value of MCCS was validated in a large cohort of various native kidney diseases [3] and has shown to predict outcomes in individual cohorts of patients with C3 glomerulopathy (C3GP) [21,22], AAV [23], MN [24], FSGS [25] and MCD [26]. Due to its prognostic value, the MCCS was implemented in the FCGG registry from 2018 across all pathology centers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a decrease in the PLA2R antibody level predicts the remission of proteinuria. In addition, studies indicated that the PLA2R titer was associated with progressive loss of kidney function and a high risk for relapse [ 24 , 25 ]. According to the Kidney Disease: Improving Global Outcomes organization (KDIGO.org), the PLA2R antibody was listed as a high-risk factor resulting in the progression to end-stage kidney disease.…”
Section: Discussionmentioning
confidence: 99%